Проблеми розвитку промисловості будівельних матеріалів і шляхи їх подолання - Слюсаренко, О. Ю. (НТУ "ХПІ", 2015)
У статті надається характеристика особливостей функціонування галузі будівельних матеріалів, розглядаються чинники, що впливають на функціонування промисловості будівельних матеріалів в Україні, визначаються проблеми, які раніше не знайшли рішення і на даний час заважають динамічному розвитку даної галузі, та пропонуються шляхи подолання проблем, що були виявлені, як на рівні держави, так і на рівні окремого підприємства.

The article provided description of the functioning of building materials, are The article provided description of the functioning of building materials, are considered factors affecting the operation of the building materials industry in Ukraine are determined by the problems that had not found a solution and now hinder the dynamic development of the industry and the ways to overcome problems that have been identified as at the state level and at the level of individual enterprises. In the current economic conditions, building materials industry is a major part of logistics construction, providing growth capital construction and technical progress through the introduction of efficient materials and designs. But there are problems that must be addressed comprehensively - both by creating favorable economic conditions at the national level and by enhancing investment and innovation at the level of individual enterprises, development of partnership and cooperation between enterprises of the industry.
Problems of development of building materials industry and ways of overcoming them
Keywords: будівельна продукція; конкурентоспроможність; українські товари; підприємства-виробники; construction materials; building products; competitiveness